PENDETEKSIAN KEMIRIPAN TEKS DESKRIPSI DIRI PADA E-RECRUITMENT KARYAWAN DENGAN METODE RABIN KARP DAN JARO WINKLER DISTANCE - Stephanie Stephanie; Dali Santun Naga; Viny Christanti Mawardi (Fakultas Teknologi Informasi Universitas Tarumanagara, 2021)
E-recruitment is a web-based application that is used to recruit employees for several available companies. The e-recruitment system has a plagiarism checker feature. Plagiarism itself has the meaning of actions that are considered fraud by taking someone's idea or writing without mentioning a reference and claiming it as their own. So that the e-recruitment application requires a plagiarism detector which functions to make it easier for companies to assess the characteristics of their prospective employees. The plagiarism checker feature applies a string matching algorithm to a text to search for common words between texts. There are several algorithms used for string matching, two of which are the Rabin-Karp and Jaro-Winkler algorithms. The Rabin-Karp algorithm is one of the algorithms that is suitable for solving multi-string pattern problems, while the Jaro Winkler Distance algorithm has advantages in terms of accuracy. An e-recruitment application with a plagiarism detection feature is developed and tested on various types of text, namely in the form of a self-description text of the prospective employee. From the experimental results, it was found that the two algorithms can be used to detect plagiarism in the applicant's self-description text, but it still has shortcomings in checking it.